CONDITIONS AND DISEASES IN THE “PORT UNHEALTHY”: MEDICAL KNOWLEDGE CONSTRUCTION HEALTH AND SOCIAL REPRESENTATIONS ABOUT DEATH IN ARICA (1880-1930) - Chávez Zúñiga, Pablo; Soto Lara, José (Revista de Historia Social y de las Mentalidades, 2015)
The purpose of this work is to explain the  sanitary context of Arica city. The epidemic  outbreaks are common during the period,  constructed the social representations of the  city as an “unsafe port”. This happened due  the present of at least the following diseases:  bubonic plague, malarial fevers and other  contagious diseases. The paper examines a  scenario with poor sanitary conditions, as  a result of weak infrastructure, such as the  sewagesystems. In that situation several  elements came together, highlighting the  development of the “social and sanitary issue”  that was expressed in a high mortality because  government institutions, such hospitals, were  considered charities.
Keywords: “Unhealthy port”; Diseases; Medical knowledge; Mortality